Compound, light control material, and temperature-responsive smart window
Patent Information
- Application Number
- JP2024125694
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-17
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-28
AI Technical Summary
【0018】 本発明に係る化合物、調光材料及び温度応答型スマートウィンドウは、下限臨界溶液温度を制御しやすい。
Smart Images

Figure 2025027996000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound, a light-controlling material, and a temperature-responsive smart window. [Background technology]
[0002] It is known that a solute dissolved in a solvent undergoes phase separation when it exceeds a certain temperature. This temperature is also called the lower critical solution temperature (hereinafter referred to as "LCST"). A representative example of a substance that has an LCST is poly(N-isopropylacrylamide) (hereinafter referred to as "PNIPAm"). In an aqueous solution, PNIPAm dissolves at temperatures lower than the LCST of 31°C and precipitates (phase separates) at temperatures higher than the LCST.
[0003] Non-Patent Document 1 reports that, as an application example of PNIPAm, PNIPAm was applied to a temperature-responsive smart window. A temperature-responsive smart window is a window capable of controlling the amount of light transmission in response to the outside temperature. Non-Patent Document 1 shows that a window formed by interposing water containing PNIPAm between glass panes becomes opaque as the temperature rises. When a temperature-responsive smart window is used as a window for a building, a car, etc., it is possible to suppress an unnecessary rise in the indoor temperature caused by incident light, and contribute to reducing the amount of energy used for cooling.
[0004] As a substance that exhibits LCST, Patent Document 1 discloses a temperature-responsive hydrogel that contains a polymer having a carboxyl group and a divalent metal salt of an organic acid. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 117165 [Non-patent literature]
[0006] [Non-Patent Document 1] Yang Zhou, 6 others, “Liquid Thermo-Responsive Smart Window Derived from Hydrogel”, Joule, 2020, 4, 2458-2474 Summary of the Invention [Problem to be solved by the invention]
[0007] When controlling the amount of light transmission according to the outside temperature, such as in temperature-responsive smart windows, it is industrially preferable to be able to control the LCST according to the application, so there is a demand for new light-controlling materials whose LCST is easy to control.
[0008] The present invention has been made in view of the above-mentioned circumstances, and has an object to provide a compound whose lower critical solution temperature is easily controlled, a light-controlling material, and a temperature-responsive smart window. [Means for solving the problem]
[0009] The compound according to the first aspect of the present invention is As shown in formula (I) below. [ka] (In formula (I), m is 2 or 3, and R 1 is hydrogen or a methyl group, R 2 is a straight or branched alkyl group having 3 or 4 carbon atoms.
[0010] The light-adjusting material according to the second aspect of the present invention comprises: It contains a compound represented by the following formula (I). [ka] (In formula (I), m is 2 or 3, and R 1 is hydrogen or a methyl group, R 2 is a straight or branched alkyl group having 2 to 6 carbon atoms.
[0011] In the light-adjusting material according to the second aspect of the present invention, R 2 is a linear alkyl group having 2 to 4 carbon atoms; This may also be the case.
[0012] In the light-adjusting material according to the second aspect of the present invention, m is 2 and R 1 is a methyl group; This may also be the case.
[0013] The light-adjusting material according to the second aspect of the present invention is Further containing polyvinyl alcohol, This may also be the case.
[0014] The degree of saponification of the polyvinyl alcohol is 86 to 90 mol%. This may also be the case.
[0015] The light-adjusting material according to the second aspect of the present invention is Further containing water as a solvent, It is an aqueous solution. This may also be the case.
[0016] The particle size of the compound in the aqueous solution before phase separation is less than 400 nm; This may also be the case.
[0017] A temperature-responsive smart window according to a third aspect of the present invention comprises: The light-adjusting material according to the second aspect of the present invention is provided. Effect of the Invention
[0018] The compound, light-controlling material, and temperature-responsive smart window according to the present invention make it easy to control the lower critical solution temperature. [Brief description of the drawings]
[0019] [Figure 1]FIG. 11 is a partial cross-sectional perspective view of a temperature-responsive smart window in accordance with a third embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the temperature dependence of the transmittance of an aqueous solution of a compound (Bu-DEG) according to an example of the present invention. [Diagram 3] FIG. 2 is a graph showing the temperature dependence of the transmittance of an aqueous solution of the compound (Et-DEG) according to the present invention. [Figure 4] FIG. 2 is a diagram showing the temperature dependence of the transmittance of an aqueous solution of a compound (Pr-DEG) according to an embodiment of the present invention. [Diagram 5] FIG. 2 is a graph showing the temperature dependence of the transmittance of an aqueous solution of a compound (Pr-TEG) according to an embodiment of the present invention. [Figure 6] FIG. 2 is a graph showing the concentration dependence of the LCST of the compounds according to the examples of the present invention. [Figure 7] 1 shows particle size distributions of a compound (Bu-DEG) according to an embodiment of the present invention, (A), (B) and (C) showing particle size distributions at 60° C., 40° C. and 10° C., respectively. [Figure 8] 1 shows particle size distributions of a compound (Pr-DEG) according to an example of the present invention, (A) and (B) showing particle size distributions at 40° C. and 10° C., respectively. [Figure 9] FIG. 1 is a diagram showing the appearances of samples 1 to 7 according to examples of the present invention after 0, 3, 6, and 12 hours. [Figure 10] FIG. 1 is a diagram showing the appearances of Samples 1 and 8 to 12 according to the examples of the present invention after 0, 3, 6 and 12 hours. [Figure 11] FIG. 13 is a diagram showing the appearance of Sample 12 one day after the temperature was lowered. [Figure 12] FIG. 2 is a diagram showing the temperature dependence of transmittance of Sample 1 according to an embodiment of the present invention. [Figure 13] FIG. 4 is a diagram showing the temperature dependence of the transmittance of Sample 2 according to an embodiment of the present invention. [Figure 14] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 4 according to an embodiment of the present invention. [Figure 15] FIG. 13 is a diagram showing the temperature dependence of the transmittance of Sample 13 according to an embodiment of the present invention. [Figure 16] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 14 according to an embodiment of the present invention. [Figure 17] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 3 according to an embodiment of the present invention. [Figure 18] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 5 according to an embodiment of the present invention. [Figure 19] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 15 according to an embodiment of the present invention. [Figure 20] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 16 according to an embodiment of the present invention. [Figure 21] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 6 according to an embodiment of the present invention. [Figure 22] FIG. 13 is a diagram showing the temperature dependence of transmittance of Sample 7 according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The embodiments of the present invention will be described with reference to the drawings. Note that the present invention is not limited to the following embodiments and drawings. Note that in the following embodiments, the expressions "have", "include" and "contain" also include the meaning of "consisting of" or "consisting of".
[0021] Embodiment 1: Compound The compound according to the present embodiment is represented by the following formula (I). In formula (I), m is 2 or 3. Preferably, m in formula (I) is 2. R in formula (I) 1 is hydrogen or a methyl group. Preferably, R 1 is a methyl group. 2 is a linear or branched alkyl group having 2 to 6 carbon atoms. 2 is a linear alkyl group having 2 to 4 carbon atoms, or a linear or branched alkyl group having 3 or 4 carbon atoms.
[0022] [ka]
[0023] R 2 When R is a linear alkyl group having 2 to 4 carbon atoms, the compound is represented by the following formula (II). In formula (II), n is 1 to 3. Preferably, in formula (II), m is 2 and R 1 is a methyl group.
[0024] [ka]
[0025] The compound according to the present embodiment can be produced by introducing an oxyethylene chain according to the size of m, for example, into tosyl chloride (Step 1), and reacting the resulting tosyl derivative with a gallic acid derivative (Step 2). In Step 1, the tosyl derivative can be synthesized by reacting tosyl chloride with diethylene glycol monomethyl ether or triethylene glycol monomethyl ether in an appropriate solvent under alkaline conditions. In Step 2, a gallic acid derivative, for example R 2 When is a linear alkyl group having 2 to 4 carbon atoms, ethyl gallate, propyl gallate or butyl gallate may be reacted with a tosyl derivative to substitute the phenolic hydroxy group for an oxyethylene chain.
[0026] The compound according to the present embodiment has an LCST in an aqueous solution in the range of about 25 to 55°C. The LCST can be evaluated, for example, by measuring the transmittance (turbidity) using an ultraviolet-visible-near infrared spectrophotometer. The LCST can also be evaluated by measuring the endothermic / heat-generating peak using a differential scanning calorimeter. Furthermore, the LCST can be evaluated by measuring the temperature dependence of the dynamic elastic modulus using a rheometer. In the present embodiment, the LCST (cloud point) is defined as the temperature at which the transmittance of light with a wavelength of 500 nm is 50% of the value at 10°C.
[0027] The LCST of the compound according to the present embodiment is R 2The amount of carbon in the alkyl group can be adjusted by changing the number of carbon atoms (alkyl chain length) of the alkyl group and the concentration of the compound in the aqueous solution. 2 The LCST decreases as the number of carbon atoms increases, and the LCST decreases as the concentration of the compound increases. Therefore, the compound according to the present embodiment can control the LCST depending on the application.
[0028] Embodiment 2: Light-adjusting material The light-adjusting material according to this embodiment contains the compound according to the first embodiment. The light-adjusting material may be, for example, in the form of a liquid or gel. Preferably, the light-adjusting material is a solution in which the compound is dissolved as a solute in a solvent. The solvent is not particularly limited as long as the compound is soluble in the solvent, but is preferably water. The light-adjusting material may further contain water as a solvent. In this case, the light-adjusting material is an aqueous solution of the compound. The gel is mainly composed of a solution of the compound and a polymer. The gel can be manufactured by a known method, for example, by using a polymerization initiator.
[0029] The light-adjusting material according to the present embodiment may contain a plurality of compounds represented by the above formula (I). For example, the light-adjusting material may be a compound represented by the formula (I) in which m is 2 and R 1 is a methyl group, and R 2 is a linear alkyl group having 3 carbon atoms; and a compound in which m in formula (I) is 2 and R 1 is a methyl group, and R 2 is a linear alkyl group having 4 carbon atoms.
[0030] When the light-modulating material is a solution of the above compound, the concentration of the compound in the solution is not particularly limited and is, for example, 0.1 to 10% by weight, 0.5 to 8% by weight, 0.8 to 6% by weight, or 1 to 5% by weight.
[0031] The light-adjusting material according to the present embodiment may further contain polyvinyl alcohol (PVA). The average polymerization degree of PVA is not particularly limited. For example, the lower limit of the average polymerization degree of PVA is 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, or 1500. For example, the upper limit of the average polymerization degree of PVA is 4000, 3900, 3800, 3700, 3600, 3500, 3400, 3300, 3200, 3100, 3000, 2900, 2800, 2700, 2600, 2500, 2400, 2300, 2200, 2100, or 2000. For example, the average polymerization degree of PVA is 400 to 600, 900 to 1000, or 3100 to 3900.
[0032] The saponification degree of PVA is not particularly limited. PVA may be a completely saponified type, but is preferably a partially saponified type. For example, the lower limit of the saponification degree of PVA is 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, or 90 mol%. For example, the upper limit of the saponification degree of PVA is 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, or 97 mol%. The saponification degree of PVA is 85 to 94 mol%, preferably 85 to 93 mol%, 85 to 92 mol%, or 85 to 91 mol%, more preferably 86 to 90 mol%.
[0033] When the light-adjusting material according to the present embodiment further contains water as a solvent, for example, the light-adjusting material may be an aqueous solution in which the above compound and PVA are dissolved as solutes in water as a solvent.
[0034] The light-adjustable material according to the present embodiment undergoes phase separation at the LCST, is transparent in a temperature range below the LCST, and is opaque in a temperature range above the LCST. Here, "transparent" means that the transmittance of light with a wavelength of 500 nm is 85% or more, and "opaque" means that the transmittance of light with a wavelength of 500 nm is 30% or less.
[0035] The particle size of the compound in the solution before phase separation is not particularly limited as long as the solution is transparent, but is, for example, less than 400 nm. When the temperature of the solution of the compound is increased to LCST or higher by heating, the particle size becomes larger and exceeds 400 nm. The particle size of the compound can be measured by sieving, sedimentation, microscopy, light scattering, laser diffraction / scattering, electrical resistance test, observation with a transmission electron microscope, observation with a scanning electron microscope, etc. The particle size may be measured by a known particle size distribution meter. The particle size can be expressed as a Stokes equivalent diameter, a circle equivalent diameter, or a sphere equivalent diameter depending on the measurement method. The particle size of the compound may be an average particle size, a volume average particle size, an area average particle size, etc., expressed as an average of a plurality of particles as the measurement object. For example, the particle size of the biocompatible particles described above may be an average particle size calculated from a volume distribution based on measurements such as laser diffraction / scattering and dynamic light scattering. Specifically, when a cumulative curve is calculated assuming the total volume of a group of particles to be 100%, the volume average particle diameter (50% diameter; D 50 ) may be used as the particle size. 50 can be determined using a commercially available particle size distribution analyzer.
[0036] Since the light-modulating material according to the present embodiment contains the above-mentioned compound having a relatively simple molecular structure, the LCST can be controlled based on the correlation between the molecular structure of the compound and the LCST.
[0037] The LCST depends on the molecular weight. The PNIPAm disclosed in Non-Patent Document 1 and the polymer disclosed in Patent Document 1 may have their molecular chains broken and their LCSTs changed when exposed to sunlight for a long period of time. On the other hand, the above compounds have a relatively simple molecular structure and are less susceptible to deterioration due to sunlight.
[0038] The light-adjusting material according to the present embodiment may contain a plurality of compounds represented by the above formula (I). For example, when the light-adjusting material contains two compounds A and B represented by the above formula (I), the LCST of the light-adjusting material can be controlled to a value between the LCST of compound A and the LCST of compound B. That is, by adjusting the mixing ratio of compound A and compound B, the LCST of the light-adjusting material can be increased or decreased.
[0039] The light-adjusting material according to the present embodiment may further contain PVA. As shown in the following examples, PVA can prolong the time that the light-adjusting material maintains its opaque state in a temperature range equal to or higher than the LCST, as compared to a case in which PVA is not included. PVA can stably maintain the opaque state of the light-adjusting material for a long period of time.
[0040] Third embodiment: Temperature-responsive smart window A temperature-responsive smart window 10 according to the present embodiment will be described with reference to FIG. 1. The temperature-responsive smart window 10 comprises glass 1, glass 2, a frame 3, and the light-control material 4 according to the above-mentioned embodiment 2. The glass 1 and glass 2 are fixed to the frame 3 as insulating glass. The light-control material 4 is enclosed in the space between the glass 1 and glass 2 and fills the space. In the temperature-responsive smart window 10, when the temperature rises and exceeds the LCST, the compound contained in the light-control material 4 undergoes phase separation and becomes cloudy, whereas when the temperature drops below the LCST, the compound dissolves and becomes transparent.
[0041] The temperature-responsive smart window 10 is preferably used as a window for buildings such as buildings, houses, and vehicles, etc. Since the LCST can be controlled based on the correlation between the molecular structure of the above compound and the LCST, the temperature-responsive smart window 10 can be provided according to a variety of usage environments and applications.
[0042] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. EXAMPLES
[0043] [Synthesis and structural analysis of compounds] Synthesis of tosyl derivatives bearing oxyethylene chains In an Erlenmeyer flask, 0.7 mol of 2-methoxyethanol, diethylene glycol monomethyl ether or triethylene glycol monomethyl ether, 1.0 mol of sodium hydroxide, 200 mL of water, and 200 mL of tetrahydrofuran (THF) were added, and the mixed solution was stirred while being cooled to 5°C or less in an ice bath. 200 mL of THF containing 0.7 mol of p-toluenesulfonyl chloride was added dropwise to the mixed solution. After the dropwise addition, the mixed solution was stirred at 5°C or less for 2 hours.
[0044] [ka]
[0045] After stirring, cold water, the reaction mixture, and dichloromethane were added to a separatory funnel and extracted. After extraction, the reaction mixture was dehydrated with anhydrous sodium sulfate and concentrated. After concentration, the mixture was purified by silica gel column chromatography using a hexane / ethyl acetate mixed solvent (1:1) as the mobile phase. The resulting hexane / ethyl acetate mixed solvent was concentrated to obtain the target product as a colorless, transparent liquid.
[0046] Synthesis of PEG-introduced gallic acid derivatives To a recovery flask were added 29 mmol of methyl gallate, ethyl gallate, propyl gallate, or butyl gallate, 91 mol of a tosyl derivative, 174 mmol of potassium carbonate, and 87 mL of N,N-dimethylformamide (DMF), and the mixture was refluxed and stirred for 15 hours while heating to 100°C.
[0047] [ka]
[0048] After stirring, water, the reaction mixture, and ethyl acetate were added to a separatory funnel and extracted. After extraction, the reaction mixture was dehydrated with anhydrous sodium sulfate and concentrated. After concentration, the mixture was purified by silica gel column chromatography using ethyl acetate as the mobile phase. The obtained ethyl acetate solvent was concentrated to obtain the target product.
[0049] structural analysis 1 H and 13 C-NMR spectra were measured using a JNM-ECA500 (JEOL Ltd., 1 H: 500MHz, 13 C: 125 MHz) and the chemical shifts are those of the internal Me 4 The values are expressed as ppm relative to Si.
[0050] Me-DEG. Yellow oil: 12.2 g (86%). 1 H-NMR (500 MHz, CDCl 3 , ppm): δ 3.38 (s, 3H), 3.39 (s, 6H), 3.53-3.59 (m, 6H), 3.68-3.76 (m, 6H), 3.80-3.84 (m, 2H), 3.86-3.90 (m, 7H), 4.22 (t, J=5 Hz, 4H), 4.25 (t, J=5Hz, 2H), 7.30 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 51.91, 58.76, 58.80, 68.56, 69.36, 70.19, 70.34, 70.49, 71.73, 71.79, 72.23, 108.62, 124.70, 142.20, 152.03, 166.30. Et-DEG. Yellow oil: 12.9 g (88%). 1 H-NMR (500 MHz, CDCl 3, ppm): δ 1.38 (t, J=7 Hz, 3H), 3.38 (s, 3H), 3.39 (s, 6H), 3.53-3.58 (m, 6H), 3.70-3.74 (m, 6H), 3.80-3.83 (m, 2H), 3.86-3.90 (m, 4H), 4.19-4.26 (m, 6H), 4.35 (q, J=7 Hz, 2H), 7.30 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 14.32, 58.97, 59.01, 61.00, 68.75, 69.57, 70.39, 70.52, 70.68, 71.92, 71.97, 72.41, 108.86, 125.31, 142.34, 152.18, 166.06.
[0051] Pr-DEG. Yellow oil: 13.4 g (89%). 1 H-NMR (500 MHz, CDCl 3 , ppm): δ 1.02 (t, J=7.5, 3H), 1.78 (t, J=7.5, 2H), 3.38 (s, 3H), 3.39 (s, 6H), 3.53-3.58 (m, 6H), 3.70-3.74 (m, 6H), 3.82 (t, J=5.0, 2H), 3.88 (t, J=5.0, 4H), 4.20-4.27 (m, 8H), 7.31 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 10.64, 22.22, 59.14, 59.18, 66.75, 68.93, 69.74, 70.56, 70.69, 70.85, 72.08, 72.14, 72.58, 109.07, 125.50, 142.54, 152.36, 166.29. Bu-DEG. Yellow oil: 12.0 g (78%). 1 H-NMR (500 MHz, CDCl 3, ppm): δ 1.03 (t, J=7.5, 3H), 1.46 (ddd, J=7.0, 2H), 1.74 (qq, J=7.5, 2H), 3.38 (s, 3H), 3.39 (s, 6H), 3.53-3.58 (m, 6H), 3.70-3.74 (m, 6H), 3.82 (t, J=5.5, 2H), 3.88 (t, J=5.0, 2H), 4.21 (t, J=5.0, 4H), 4.24 (t, J=5.0, 2H), 4.29 (t, J=6.5, 2H), 7.29 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 10.46, 22.05, 58.94, 66.53, 68.78, 69.55, 70.46, 70.49, 70.61, 70.74, 71.85, 72.32, 108.95, 125.25, 142.46, 152.20, 166.07.
[0052] Pr-EG. Yellow oil: 10.3 g (92%). 1 H-NMR (500 MHz, CDCl 3 , ppm): δ 1.02 (t, J=7 Hz, 3H), 1.78 (sext, J=7 Hz, 2H), 3.44 (s, 3H), 3.45 (s, 6H), 3.70-3.74 (m, 2H), 3.76-3.79 (m, 4H), 4.18-4.24 (m, 6H), 4.25 (t, J=7 Hz, 2H), 7.33 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 10.46, 22.06, 58.81, 59.10, 66.58, 68.90, 70.94, 71.80, 72.24, 109.36, 125.40, 142.76, 152.33, 166.13. Pr-TEG. Yellow oil: 14.7 g (78%). 1 H-NMR (500 MHz, CDCl 3, ppm): δ 1.02 (t, J=7 Hz, 3H), 1.78 (sext, J=7 Hz, 2H), 3.37 (s, 3H), 3.38 (s, 6H), 3.52-3.56 (m, 6H), 3.62-3.68 (m, 12H), 3.70-3.75 (m, 6H), 3.78-3.82 (m, 2H), 3.86-3.89 (m, 4H), 4.18-4.24 (m, 6H), 4.25 (t, J=7 Hz, 2H), 7.30 (s, 2H). 13 C-NMR (125 MHz, CDCl 3 , ppm): δ 10.48, 22.07, 58.97, 58.98, 66.59, 68.78, 69.57, 70.48, 70.51, 70.63, 70.76, 71.87, 72.34, 108.96, 125.30, 142.45, 152.21, 166.12.
[0053] [Evaluation of LCST of compounds and measurement of particle size] Transmittance measurement Gallic acid derivatives were dissolved in water at a specified concentration to prepare samples. The transmittance of the samples was measured using a V-630 (manufactured by JASCO Corporation) equipped with a temperature control function. The sample was placed in a quartz cell (optical path length 1 cm), and the temperature was changed from 10 to 60°C at a rate of 1.0°C / min, and the transmittance of light with a wavelength (λ) of 500 nm was recorded at measurement intervals of 1°C.
[0054] (result) The temperature dependence of the transmittance of 3 wt% aqueous solutions of Bu-DEG, Et-DEG, Pr-DEG, and Pr-TEG when they were cooled from a high temperature and heated from a low temperature are shown in Figures 2, 3, 4, and 5. Table 1 shows the solubility of each compound in water and the LCST, which is the temperature at which the transmittance of light with a wavelength of 500 nm reaches 50% of the value at 10°C. It was shown that the LCST tends to decrease as the length of the alkyl chain in the compound increases, that is, as n increases.
[0055] [Table 1]
[0056] The concentration dependence of the LCST of each compound in aqueous solution upon cooling or heating is shown in Figure 6. It was shown that the LCST tends to decrease as the compound concentration increases.
[0057] Particle size distribution measurement The particle size of the sample was measured by dynamic light scattering (DLS) using a zetasizer μV (Malvern Panalytical). The sample was placed in a quartz cell (light path length 1 cm) and held at a specified temperature for 10 minutes before starting the measurement.
[0058] (result) Figures 7(A), 7(B), and 7(C) show the particle size distributions of Bu-DEG in a 3 wt % aqueous solution at 60° C., 40° C., and 10° C., respectively. It was shown that before phase separation, aggregates of 375 nm were formed, and after phase separation, the aggregates aggregated and the particle size increased. The particle size distributions of Pr-DEG in a 3 wt% aqueous solution at 40° C. and 10° C. are shown in Figures 8(A) and 8(B), respectively. Similar to Bu-DEG, aggregates of 138 nm were formed before phase separation, and after phase separation the aggregates aggregated to a particle size of 437 nm.
[0059] [Investigation of the duration of cloudiness when left standing] Sample preparation 20 mL of distilled water and 1.02 g of PVA were added to a 50 mL recovery flask and stirred overnight under reflux. After confirming that the PVA was completely dissolved in the distilled water, the solution was allowed to cool to room temperature and poured into a 50 mL measuring flask to prepare a 2 wt% PVA aqueous solution. PVA includes PVA500 fully saponified type (165-16315, average degree of polymerization about 400-600, saponification degree 96 mol% or more, Fujifilm Wako Pure Chemical Industries, Ltd.), PVA1000 fully saponified type (162-16325, average degree of polymerization about 900-1000, saponification degree 96 mol% or more, Fujifilm Wako Pure Chemical Industries, Ltd.), PVA500 partially saponified type (163-03045, average degree of polymerization about 500, saponification degree 86-90 mol%, Fujifilm Wako Pure Chemical Industries, Ltd.), PVA1000 partially saponified type (169-16335, average degree of polymerization about 900-1000, saponification degree 86-90 mol%, Fujifilm Wako Pure Chemical Industries, Ltd.), PVA1500 Partially saponified type (160-03055, average degree of polymerization about 1500, saponification degree 86 to 90 mol%, Fujifilm Wako Pure Chemical Industries, Ltd.) and PVA3500 partially saponified type (163-16355, average degree of polymerization about 3100 to 3900, saponification degree 86 to 90 mol%, Fujifilm Wako Pure Chemical Industries, Ltd.) were used.
[0060] For comparison, a 2 wt % aqueous solution of ethanol, a 2 wt % aqueous solution of ethylene glycol, a 2 wt % aqueous solution of 1,3-butanediol, a 2 wt % aqueous solution of 1,4-butanediol and a 1 wt % aqueous solution of methylcellulose were prepared.
[0061] Temperature retention test 5 mL of 3 wt% Pr-DEG solution was prepared using distilled water, the 2 wt% PVA aqueous solution prepared above, 2 wt% ethanol aqueous solution, 2 wt% ethylene glycol aqueous solution, 2 wt% 1,3-butanediol aqueous solution, 2 wt% 1,4-butanediol aqueous solution, and 1 wt% methylcellulose aqueous solution as solvents. In detail, the solvents shown in Table 2 were added to a 5 mL eggplant flask containing 155 mg of Pr-DEG. 5 mL of the prepared 3 wt% Pr-DEG solution (samples 1 to 12) was placed in a 10 mL test tube, and the temperature of the test tube was kept at 50°C for a predetermined time using a thermostatic water bath (BK300, Yamato Scientific Co., Ltd.).
[0062] [Table 2]
[0063] (result) FIG. 9 shows the state of samples 1 to 7 after 0, 3, 6, and 12 hours. The opacity of sample 3 became lighter after 3 hours. The opacity of sample 1 became lighter after 6 hours. The opacity of sample 2 became lighter after 12 hours. For samples 4 to 7, the opacity was maintained even after 12 hours. FIG. 10 shows the state of samples 1 and 8 to 12 after 0, 3, 6, and 12 hours. The opacity of samples 1 and 8 to 11 became lighter after 6 hours. The opacity of sample 12 was maintained even after 12 hours. FIG. 11 shows the state of sample 12 after one day of being held at 50°C and then cooled to room temperature. Sample 12 did not return to transparency.
[0064] [Evaluation of LCST of samples containing PVA] Sample preparation 3 mL of distilled water and 417 mg of PVA were added to a 10 mL recovery flask and stirred overnight under reflux. After confirming that the PVA was completely dissolved in the distilled water, the solution was allowed to cool to room temperature and poured into a 10 mL measuring flask to prepare a 4 wt% PVA aqueous solution. The PVA used was the above-mentioned PVA500 fully saponified type, PVA500 partially saponified type, PVA1000 fully saponified type, and PVA1000 partially saponified type.
[0065] Transmittance measurement In addition to the above samples 1 to 7, 3 wt% Pr-DEG solutions were prepared using a 4 wt% PVA aqueous solution as the solvent (sample 13: fully saponified 4 wt% PVA500 solvent; sample 14: partially saponified 4 wt% PVA500 solvent; sample 15: fully saponified 4 wt% PVA1000 solvent; sample 16: partially saponified 4 wt% PVA1000 solvent). The transmittance of the aqueous solutions was measured using the method described above when repeatedly heated from a low temperature and cooled from a high temperature, and the temperature dependence was evaluated.
[0066] (result) The temperature dependence of transmittance of each of Samples 1, 2, 4, 13, 14, 3, 5, 15, 16, 17, 18, 19, 20, 21 and 22 are shown in Figures 12, 13, 14, 15, 16, 17, 18, 19, 20, 21 and 22. PVA had almost no effect on the LCST.
[0067] The present invention allows various embodiments and modifications without departing from the broad spirit and scope of the present invention. The above-described embodiments are for the purpose of explaining the present invention and do not limit the scope of the present invention. That is, the scope of the present invention is indicated by the claims, not the embodiments. Various modifications made within the scope of the claims and the scope of the invention equivalent thereto are considered to be within the scope of the present invention. [Industrial Applicability]
[0068] The present invention is useful for light control materials, particularly for temperature-responsive smart windows. [Explanation of symbols]
[0069] 1,2 Glass 3 Slots 4. Photochromic Materials 10 Temperature-responsive smart windows
Claims
1. A compound represented by the following formula (I): 【Chemistry 1】 In formula (I), m is 2 or 3, and R 1 is hydrogen or a methyl group, R 2 is a straight or branched alkyl group having 3 or 4 carbon atoms.
2. Contains a compound represented by the following formula (I): Photochromic material. 【Chemistry 2】 In formula (I), m is 2 or 3, and R 1 is hydrogen or a methyl group, R 2 is a straight or branched alkyl group having 2 to 6 carbon atoms.
3. R 2 is a linear alkyl group having 2 to 4 carbon atoms; The light-adjusting material according to claim 2 .
4. m is 2, R 1 is a methyl group; The light-adjusting material according to claim 3 .
5. Further containing polyvinyl alcohol, The light-adjusting material according to claim 2 .
6. The degree of saponification of the polyvinyl alcohol is 85 to 94 mol%. The light-adjusting material according to claim 5 .
7. Further containing water as a solvent, It is an aqueous solution. The light-adjusting material according to claim 2 .
8. The particle size of the compound in the aqueous solution before phase separation is less than 400 nm; The light-adjusting material according to claim 7.
9. The light-adjusting material according to any one of claims 2 to 6 is provided. Temperature responsive smart window.
Citation Information
Patent Citations
Temperature-responsive gel having LCST with no volume phase transition, and production method therefor
WO2018117165A1